Taking a Partnered Approach to Managing Academic Stress: An Undergraduate Study. Issue 4 (1st October 2020) - Turner, Michelle; Simmons, Denise R.
ABSTRACT: The ability to positively adapt to situations of stress and adversity enables student progress, growth, and learning. In the context of undergraduate building and construction education in the United States, little is known about the resources necessary for students to manage stressors associated with their studies. Twenty undergraduate building and construction students from a large, public land-grant university in the United States were interviewed. Inductive thematic analysis was used to explore the antecedents and impacts of academic stress, and deductive thematic analysis was used to identify resilience-building resources using the Resilience at University (RAU) framework. Resources identified to reduce stressor severity were focused on modifying the learning environment and implementing a scaffolded approach to learning and skills development. Resilient-building resources aligned with the six dimensions of the RAU were identified at the student level and the university level. An important contribution is the pivotal role of the student–university partnership in managing academic stress and building student resilience capability, acknowledging both students and the university as key actors. The findings will be of interest to educators and students who can implement a partnered approach to reduce the prevalence of academic stressors together with building students' capacity to manage stress.